Factors influencing casualty risk in the 14th November 2016 MW7.8 Kaikōura, New Zealand earthquake. (December 2020) - Horspool, Nick; Elwood, Ken; Johnston, David; Deely, Joanne; Ardagh, Michael
Abstract: The November 14, 2016 MW 7.8 Kaikōura Earthquake was one of the largest earthquakes to occur in New Zealand in the past 100 years and resulted in two deaths and 618 injuries. Understanding the context and cause of casualties from earthquakes is important for informing risk reduction activities such as building codes, education of protective actions, and casualty modelling. Data on casualties (deaths and injuries) from the Kaikōura earthquake were sourced from New Zealand's publicly funded accidental injury insurance scheme. Casualties were compared to a control group of uninjured people using a case-control design. Odds ratios were calculated through multivariate logistic regression to quantify the influence of individual, seismological and contextual factors on casualty risk. Females were twice as likely to be injured than males, and injury risk increased 30% with every 10 year increase in age. People were 2.9 times more likely to be injured if they were in non-residential buildings, and injury risk increased 2.2 times for every unit increase in MMI shaking intensity. Thirty-seven percent of casualties were from falls, 44% were from actions of people during shaking and 8% were due to being hit by contents. Nine percent of people were injured after shaking stopped during evacuations, or clean-up. The results indicate that in regions with a well-regulated building industry with modern building codes such as New Zealand, casualties are dominated by non-fatal injuries, and the number of these injuries are determined by the behaviour of individuals during and immediately following earthquake shaking.